2013
DOI: 10.1007/s00213-013-3395-z
|View full text |Cite
|
Sign up to set email alerts
|

Dexamphetamine effects on prepulse inhibition (PPI) and startle in healthy volunteers

Abstract: Results indicate that sex differences exist in motor, but not sensory, components of the startle reflex. Findings also reveal that administration of 0.45 mg/kg dexamphetamine to healthy humans does not mimic PPI effects observed in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In line with this, our recent experiments with mephedrone, nor-mephedrone, and MDPV showed comparable weak or negative effects on PPI in rats (unpublished observations Horsley et al and Sichova et al). Interestingly amphetamine, which is approximately 10 times more potent in disrupting PPI in rodents, in humans also failed to have disruptive effect on PPI ( 41 ). However, this might be related to the fact that it was used in much lower dose (0.45 mg/kg) in humans compared with rodents (typically 1–4 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, our recent experiments with mephedrone, nor-mephedrone, and MDPV showed comparable weak or negative effects on PPI in rats (unpublished observations Horsley et al and Sichova et al). Interestingly amphetamine, which is approximately 10 times more potent in disrupting PPI in rodents, in humans also failed to have disruptive effect on PPI ( 41 ). However, this might be related to the fact that it was used in much lower dose (0.45 mg/kg) in humans compared with rodents (typically 1–4 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…In one session, participants were given a single dose of dexamphetamine sulfate (Sigma Pharmaceuticals Pty Ltd., Victoria, Australia) at 0.45 mg/kg (to the nearest 2.5 mg) in oral capsule form. This research group has demonstrated that administration of this dose of dexamphetamine induces changes in multiple behavioral (Albrecht et al, ; Chitty et al, ) and physiological markers (Albrecht, Price, Lee, Iyyalol, & Martin‐Iverson, ; Albrecht et al, ). The mean weight and dose of participants are given in Table .…”
Section: Methodsmentioning
confidence: 99%
“…More details on the model are provided in Supporting Information and the models are an extension of those used in previous publications [Chitty et al, ; Lam et al, ]. The prior for the overall effect of dexamphetamine was described by a normal distribution centered on 0 with a standard deviation equal to 1, i.e., it was anticipated that regardless of the direction of the effect of dexamphetamine, the effect size was most likely to be well within 1–2 standard deviations of the difference scores.…”
Section: Methodsmentioning
confidence: 99%